SEMINAR PEMERIKSAAN DENGAN METODE REAL TIME POLYMERASE CHAIN REACTION ASSAY (RT-PCR) SEBAGAI TES CEPAT MYCOBACTERIUM TUBERCULOSIS DARI SAMPEL DAHAK PASIEN TUBERCULOSIS DI PUSKESMAS LUBUK PAKAM - Suventi Syafrina Ginting; Visensius Krisdianilo (JURNAL PENGMAS KESTRA (JPK), 2021)
Mycobacterium tuberculosis is known as a highly pathogenic bacterium. These bacteria are aerobic in shape like rods and have resistance to acids. These bacteria can cause tuberculosis (TB). TB disease has been widely known as a fairly high cause of death in the world. Tuberculosis causes the death of nearly one million women each year. Currently not a single country in the world has been free of tuberculosis. Data shows that Indonesia is the third largest contributor to tuberculosis cases in the world. Examination of mycobacterium tuberculosis bacteria that are routinely performed in hospitals or health centers is using microscopic diagnosis of acid-resistant basil (BTA). Recently there has been a quick test of Mycobacterium tuberculosis using the semi-quantitative Real Time Polymerase Chain Reaction Assay (RT-PCR) method that targets the rpoB gene in Mycobacterium tuberculosis, which can automatically process preparations by extraction of doxyribo nucleic acid (DNA) in catridge. Rt-PCR test results are very specific in detecting Mycobacterium tuberculosis. There are some results that are not detected with microscopic examination (BTA) can be detected by RT-PCR technique. However, overall there is no significant difference in results between microscopic methods and RT-PCR. As well as seminar participants can follow and understand the materials submitted and also the examination procedures carried out.